Konsep Pencegahan Fraud: Berdasarkan Pada Pemahaman “Skizofrenia” dan Psy-Complex Theory - Ybanez Vijeysechan Hamadi; Iwan Triyuwono; Ali Djamhuri (Universitas Muhammadiyah Malang, 2024)
Purpose: The objective of this research is to formulate a fraud prevention concept based on psychological dynamics of fraud committers. Methodology/approach: This postmodernism research uses a case study approach regarding the psychological processes of fraud committers which are similar to the metaphor of “Schizophrenia”. The data of this research was acquired from interviews with fraud committers, an observer, and a person with authority. The analysis was conducted using psy-complex theory, which consists of psychoanalysis and psychotherapy methods. Findings: This study finds that economic and social pressure contribute to the vulnerability of showing symptoms similar to the metaphor “schizophrenia” will get more severe (the fixated phase). This condition increases the tendency of individuals to engage in activities that are not based on logical reasoning. Therefore, the formulation of fraud prevention concept that is based on the balance in psychological dynamics, between the elements of mind, conscience, and behavior, can be used to recover human’s mental wellbeing. Practical implications: The fraud act can be committed by anyone. The regulations relating to mental health need to be considered, it’s important part of reducing an individual's motivation to cheat. Originality/value: The formulation of a fraud prevention concept rooted in the balance of human psychology, between the mind, conscience, and behaviour